Gallbladder Polyps: Epidemiology, Natural History and Management - Robert P Myers; Eldon A Shaffer; Paul L Beck (Canadian Journal of Gastroenterology)
Polypoid lesions of the gallbladder affect approximately 5% of the adult population. Most affected individuals are asymptomatic, and their gallbladder polyps are detected during abdominal ultrasonography performed for unrelated conditions. Although the majority of gallbladder polyps are benign, most commonly cholesterol polyps, malignant transformation is a concern. The differentiation of benign from malignant lesions can be challenging. Several features, including patient age, polyp size and number, and rapid growth of polyps, are important discriminating features between benign and malignant polyps. Based on the evidence highlighted in this review, the authors recommend resection in symptomatic patients, as well as in asymptomatic individuals over 50 years of age, or those whose polyps are solitary, greater than 10 mm in diameter, or associated with gallstones or polyp growth on serial ultrasonography. Novel imaging techniques, including endoscopic ultrasonography and enhanced computed tomography, may aid in the differential diagnosis of these lesions and permit expectant management.